How can qualitative in-depth interviews optimize cross-cultural measurement of academic resilience? - Liu, Tian Fang; Fan, Song Ching; Le Jiang, Xin (Frontiers in Psychology, 2025)
This study explores how qualitative in-depth interviews can optimize the measurement of academic resilience across cultures, addressing the challenges faced by Chinese university students in academic setbacks. Employing a mixed-methods approach, we conducted in-depth interviews analyzed through grounded theory using Nvivo 14 and developed a measurement scale for academic resilience among Chinese students. Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) using IBM SPSS AMOS 28 were performed to validate the scale’s psychometric properties. The findings reveal that Chinese students exhibit unique cultural traits in coping with academic setbacks, such as face-saving concerns, guilt, self-blame, and a preference for stability. Their coping strategies involve self-reflection, cognitive restructuring, and external support seeking, shaped by cultural influences. The Chinese University Students’ Academic Setback Resilience Scale (CUSASRS) comprises dimensions of proactive coping strategies, learning engagement, and perceptions of academic adversity, offering a comprehensive representation of psychological and behavioral responses. This study contributes to understanding the cultural influences on academic resilience among Chinese students and provides empirical evidence for scale design and intervention strategies.